The Multivalent Role of Fibronectin-Binding Proteins A and B (FnBPA and FnBPB) of Staphylococcus aureus in Host Infections - Speziale, Pietro (Front Microbiol, 2020)
Staphylococcus aureus, one of the most important human pathogens, is the causative agent of several infectious diseases including sepsis, pneumonia, osteomyelitis, endocarditis and soft tissue infections. This pathogenicity is due to a multitude of virulence factors including several cell wall-anchored proteins (CWA). CWA proteins have modular structures with distinct domains binding different ligands. The majority of S. aureus strains express two CWA fibronectin (Fn)-binding adhesins FnBPA and FnBPB (Fn-binding proteins A and B), which are encoded by closely related genes. The N-terminus of FnBPA and FnBPB comprises an A domain which binds ligands such as fibrinogen, elastin and plasminogen. The A domain of FnBPB also interacts with histones and this binding results in the neutralization of the antimicrobial activity of these molecules. The C-terminal moiety of these adhesins comprises a long, intrinsically disordered domain composed of 11/10 fibronectin-binding repeats. These repetitive motifs of FnBPs promote invasion of cells that are not usually phagocytic via a mechanism by which they interact with integrin α(5)β(1) through a Fn mediated-bridge. The FnBPA and FnBPB A domains engage in homophilic cell-cell interactions and promote biofilm formation and enhance platelet aggregation. In this review we update the current understanding of the structure and functional properties of FnBPs and emphasize the role they may have in the staphylococcal infections.